2020
DOI: 10.1002/anie.202003563
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Aptamers for Molecular Diagnostics and Therapeutics: Advances and Perspectives

Abstract: The advent of SELEX (systematic evolution of ligands by exponential enrichment) technology has shown the ability to evolve artificial ligands with affinity and specificity able to meet growing clinical demand for probes that can, for example, distinguish between the target leukemia cells and other cancer cells within the matrix of heterogeneity, which characterizes cancer cells. Though antibodies are the conventional and ideal choice as a molecular recognition tool for many applications, aptamers complement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
165
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(169 citation statements)
references
References 109 publications
(14 reference statements)
0
165
0
4
Order By: Relevance
“…As an alternative to the enzyme and to improve selectivity, aptamers are used as biorecognition elements in sensors. Aptamers are short DNA or RNA strands that are selected using a technique known as SELEX (systematic evolution of ligands by exponential enrichment) have been widely employed in many biosensors for the detection of biomarkers, pathogens, and diagnosis of serious diseases [70][71][72][73]. To improve the specificity of pesticide sensors, pesticide-specific aptamer coupled with CQDs have been reported as a probe for the detection of acetamiprid [74].…”
Section: Review Articlementioning
confidence: 99%
“…As an alternative to the enzyme and to improve selectivity, aptamers are used as biorecognition elements in sensors. Aptamers are short DNA or RNA strands that are selected using a technique known as SELEX (systematic evolution of ligands by exponential enrichment) have been widely employed in many biosensors for the detection of biomarkers, pathogens, and diagnosis of serious diseases [70][71][72][73]. To improve the specificity of pesticide sensors, pesticide-specific aptamer coupled with CQDs have been reported as a probe for the detection of acetamiprid [74].…”
Section: Review Articlementioning
confidence: 99%
“…Nowadays, several other analytical approaches, such as capillary electrophoresis [ 15 ], particle display technology [ 16 ], and microfluidic chips [ 17 ], have been introduced along with the SELEX process, to improve the efficiency of the selection procedure. Moreover, it has become possible to add multiple functional moieties onto the aptamers through automated modular synthesis, computational technologies, and phosphoramidite chemistry [ 18 ]. For example, Meng Liu et al (2019) reported the selection of two high affinity DNA aptamers from the circular libraries [ 19 ], against the glutamate dehydrogenase (GDH) of Clostridium difficile .…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers have gained considerable attention as artificial bioreceptors for bioanalytical and therapeutic applications, as they offer several advantages relative to antibodies, such as high chemical stability, low batch-to-batch variation, and economical synthesis ( 3 , 4 ). Due to these and other advantageous properties, there has been increasing interest in the use of aptamers as probes for detecting small molecules relevant for biomedical research applications, medical diagnostics, therapeutic drug monitoring and drug testing ( 3 , 5 ), as well as the in-depth study of biological systems such as neurotransmission ( 6 ) and gene expression ( 7 ). For example, aptamers were recently employed for real-time monitoring of the pharmacokinetics of small-molecule drugs in the circulation of live animals ( 8 ).…”
Section: Introductionmentioning
confidence: 99%